2022
DOI: 10.1093/mtomcs/mfac090
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the K isotope composition of Göttingen minipig brain regions, and implications for Alzheimer's disease

Abstract: Natural stable metal isotopes have shown utility in differentiation between healthy and diseased brain states (e.g. Alzheimer's disease, AD). While the AD brain accumulates some metals, it purges others, namely K (accompanied by increased serum K, suggesting brain-blood transferal). Here, K isotope compositions of Göttingen minipig brain regions for two AD models at mid-life are reported. Results indicate heavy K isotope enrichment where amyloid beta (Aβ) accumulation is observed, and this enrichment correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…The most notable effect of AD on Cu concentration was observed in the brain stem, in which both the young and aged mice showed a significant trend towards a higher Cu content. The dysregulated Cu homeostasis in the brain stem of AD transgenic mice could be an indication that the brain stem is affected in an initial stage during the pathogenesis of AD, in contrast to earlier beliefs about the hippocampus that were hypothesized in previous works [54,55]. Although AD does not seem to affect the δ 65 Cu value of the brain stem, age seems to exert a significant effect on the isotopic composition in healthy controls.…”
Section: Discussionmentioning
confidence: 74%
“…The most notable effect of AD on Cu concentration was observed in the brain stem, in which both the young and aged mice showed a significant trend towards a higher Cu content. The dysregulated Cu homeostasis in the brain stem of AD transgenic mice could be an indication that the brain stem is affected in an initial stage during the pathogenesis of AD, in contrast to earlier beliefs about the hippocampus that were hypothesized in previous works [54,55]. Although AD does not seem to affect the δ 65 Cu value of the brain stem, age seems to exert a significant effect on the isotopic composition in healthy controls.…”
Section: Discussionmentioning
confidence: 74%
“…Mahan et al. ( 8 ) studied the K isotope composition of brains from Göttingen minipigs and its implication by Alzheimer’s disease in humans. K isotope ratios for various minipig brain regions were found to range from −0.80 to −0.34‰, with a variability of ∼0.5‰ between different brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…It has three naturally occurring isotopes: 39 K (93.258%), 40 K (0.012%) and 41 K (6.730%). To date, although very few studies have done K isotope analysis in biological samples, K isotope ratios have shown much larger variations than geological samples (7)(8)(9). For instance, terrestrial plants show large K isotope differences between C 3 (d 41 K = −1.06 to -0.15‰) and C 4 plants (d 41 K = +0.28 to 1.15‰) (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study comparing splenic artery and neuromodulation between mice, rats, pigs, and humans indicated that the pig was the most suitable model for investigating human splenic innervation [ 5 ]. Göttingen minipigs were implicated in radiation-induced coagulopathy and Alzheimer’s disease recently [ 6 , 7 ]; WZS minipigs were used for an alloxan toxicity test and Islet isolation and purification in a diabetes simulation experiment [ 8 , 9 ]; therefore, minipigs acted as a good model for investigating the human immune system.…”
Section: Introductionmentioning
confidence: 99%